Seduction as instruction: the female author as Pygmalion in long Eighteenth-Century quixotic novels - Borham-Puyal, Miriam (Journal of English Studies, 2017)
Don Quixote played a crucial role in the shifts in taste and ideology that occurred during the long eighteenth century, being an instrument for authors to validate their own work in contrast with the production of others. New didactic works displayed the need to overcome the romantic supersystem that previous authors offered and even the patriarchal or colonial canon that had been established. The present article will focus on two women writers, Tabitha Tenney and Mary Brunton, who with a story of literary and literal seductions raised their pens against a non-questioned romantic integration in didactic novels and who even converted prior canonical cervantean authors in the origin of their heroines’ quixotism.